Short communication on the comprehensive review “Contemporary Food Design from Tradition to Technology” - Ku Samsu, Ku Hasnita; Yang, Zongpu; Ab Karim, Muhammad Shahrim (Taylor’s University, 2024)
Food has changed through different eras, and how food is presented has changed dramatically. According to Rajan (2023), food is embedded in the culture of the people and spread of people through methods such as colonization and migration. Food design has been used to gain more revenue from product innovation in the catering industry and is widely used in catering businesses. This study highlights the application of food design in multiple dimensions (XIA et al., 2024); for example, food plating technology and 3D printing technology are skillfully applied in catering-related businesses, this fusion of traditional food creativity and food printing technology not only enriches the diners' dual experience of food but also benefits special populations with special dietary needs.